Pengaruh Perubahan Iklim Terhadap Produksi Tanaman Kentang. Studi kasus: di Lembang, Jawa barat - Anindita, Sastrika; Arifin, Mahfud; Sandrawati, Apong (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
The potential impacts of global warming on agricultural production warrant careful consideration, as they could pose threats to food security. This study aims to evaluate the effects of global warming on potatoes in the Lembang region, West Java, where is renowned for its horticultural production. We used climate data taken from Coordinated Regional Climate Downscaling Experiment for Southeast Asia (CORDEX-SEA), using MPI-ESM-LR_REMO2015 model under the Representative Concentration Pathway (RCP8.5) scenario. Addititionally, potato crop yield was simulated Ausing Aquacrop software. The results showed that the potential yield under the influence of climate change increased potato yield by 16%. The study identified that the increase of temperature in Lembang has positive impact on potato production